Effect of Hibiscus sabdariffa supplementation on renal function and lipidic profile in obese rats - Melchert, Alessandra [UNESP]; Rosa, Andressa Canuto [UNESP]; Genari, Vanessa [UNESP]; Frontana, Marina Salvador Gonzales [UNESP]; Da Costa Reis, Rodrigo Prandini [UNESP]; Guimarães Okamoto, Priscylla Tatiana Chalfun [UNESP]; Amaro, João Luiz [UNESP]; Rahal, Sheila Canevese [UNESP] (Science Alert, 2016)
Background and Objective: Obesity has emerged as a major public health problem and may be associated with chronic kidney diseases. Thus, this study aimed to evaluate the Hibiscus sabdariffa effects in the renal function and lipid profile in rats with obesity induced by high fat diet. Materials and Methods: Fifty two Wistar male rats were allocated into four groups (n = 13): Control: Fed with commercial rat chow and water intake, Hibiscus: Commercial rat chow and Hibiscus in aqueous solution intake, obese: High fat diet and water intake, obese+Hibiscus: High fat diet and Hibiscus in aqueous solution. The rats were weighted at 1st, 4th, 8th, 12th and 16th weeks. Urinary protein:creatinin ratio and creatinin clearance were measured at 8th and 16th weeks. After 16 weeks the rats were euthanized and serum urea, creatinine, triglyceride, total cholesterol, low-density lipoprotein (LDL)-cholesterol, high-density lipoprotein (HDL)-cholesterol, sodium, potassium, chloride and calcium were evaluated. Results: Hibiscus significantly reduced weight gain in high fat diet rats. Obese and obese+Hibiscus groups showed lower serum urea than control and hibiscus groups. Creatinin clearance was lower in obese than in control and Hibiscus groups at 16th week. Urinary protein:creatinin ratio in obese tended to be higher than in control, Hibiscus and obese+Hibiscus groups at 8th and 16th weeks. Hibiscus and obese+Hibiscus groups showed increased levels of serum sodium and chloride. Serum LDL increased and HDL decreased were observed in obese group, while obese+Hibiscus showed no HDL reduction. Decrease in LDL levels was observed in Hibiscus and obese+Hibiscus groups. Hibiscus reduced triglycerides levels in Hibiscus group. Conclusion: The nephropathy associated with obesity in the obese Wistar rat model can be reduced by Hibiscus sabdariffa supplementation. The protective effect of Hibiscus was associated with lipidic profile improvement, as well as correction of a marked reduction in glomerular filtration rate.
Keywords: Chronic kidney disease; Creatinine clearance; Dyslipidemia; Hibiscus sabdariffa L; High fat diet; Lipidic profile; Obesity; Rats; Renal parameters; Rodents; Roselle